2021
DOI: 10.1002/inf2.12219
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic overall water splitting by graphitic carbon nitride

Abstract: Photocatalytic overall water splitting (OWS) without using any sacrificial reagent to realize H2 and O2 production in the stoichiometric ratio of 2:1 is viewed as the “holy grail” in the field of solar fuel production. Developing stable, low cost, and nontoxic photocatalysts that have satisfactory solar‐to‐hydrogen conversion efficiency is of significance but challenging for realizing the large‐scale use of this sustainable technology. Among various photocatalysts, graphitic carbon nitride (GCN) has shown grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 188 publications
(258 reference statements)
0
61
0
Order By: Relevance
“…Therefore, it provides very powerful oxidation and reduction ability. Another study found that 3D g-C3N4 showed increased exciton resolution, better mobility and separation of charge carriers than g-C3N4 nanosheets, which implies the way for more electron transport in 3D morphology [60]. In particular, g-C3N4 nanosheets had a notably reduction in activity (less than 44%) because of the accumulation of nanosheets, while 3D g-C3N4 did not show significant inactivation, which confirms its high stability for the overall water splitting reaction [61].…”
Section: Metal-based Vanadate Photocatalystsmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, it provides very powerful oxidation and reduction ability. Another study found that 3D g-C3N4 showed increased exciton resolution, better mobility and separation of charge carriers than g-C3N4 nanosheets, which implies the way for more electron transport in 3D morphology [60]. In particular, g-C3N4 nanosheets had a notably reduction in activity (less than 44%) because of the accumulation of nanosheets, while 3D g-C3N4 did not show significant inactivation, which confirms its high stability for the overall water splitting reaction [61].…”
Section: Metal-based Vanadate Photocatalystsmentioning
confidence: 85%
“…One of the most important fuels is hydrogen, which is a promising and renewable chemical fuel due to its high energy density and environmentally friendly [99]. Clean generation of H2 by water splitting using a semiconductor photocatalyst and solar energy, without relying on fossil reserves, is a new technology [60] which is a target pursued by chemists over the past decade. Half of the solar energy at the earth surface is in the visible region (400<λ<800 nm), so the efficient use of visible light is essential to achieve large-scale practical H2 production by photocatalytic water splitting [100].…”
Section: Water Splittingmentioning
confidence: 99%
“…In the long term, it is not practical for large‐scale production of solar fuels, especially in the cases where the cost of sacrificial agents is even higher than produced energy itself, and the conversion products of some sacrificial agents maybe cause environmental problems. [ 413 ] Therefore, photocatalytic overall water splitting is particularly desirable. In the photocatalytic overall water splitting process, the high overpotential and activation energy as well as sluggish kinetics especially for the O 2 evolution half‐reaction enable it to be dynamically difficult to proceed.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] As such, photocatalyst must possess an appropriate electronic band structure and superior light absorption coefficient to maximize the harvesting and utilization of solar photons. [ 10 ] Intrinsically, appreciable amount of photoinduced electrons and holes will migrate to the surface of photocatalyst to undergo redox reactions. [ 11 ] Moreover, the energetic level of band structure needs to straddle the redox potential of the desired reactions, thus fulfilling the requirement of both thermodynamics and kinetics for highly efficient photocatalytic reactions.…”
Section: Introductionmentioning
confidence: 99%